The Revised Statutes of the State of Maine Passed October 22, 1840 to Which are Prefixed the Constitutions of the United States and of the State of Maine, and to Which are Subjoined the Other Public Laws of 1840 and 1841, with an Appendix Page 697, Image 713 (1841) § 4 - (:unkn) unknown (General Publisher, 1834)
If any person shall carry on the business of manufacturing gun powder, or of mixing or grinding the composition therefor, in any building within eighty rods from any valuable building, erected at the time when such business may be commenced the building, in which such business may be carried on as aforesaid, shall be deemed a public nuisance; and such person shall be liable to be prosecuted and indicted accordingly.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER